On the Usefulness of Erazm Rykaczewski’s Słownik języka polskiego in Research on the Territorial Diversification of Old Polish (Preliminary Remarks) - Piotrowska-Wojaczyk, Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2023)
The aim of the article is to demonstrate the usefulness of Erazm Rykaczewski’s Słownik języka polskiego for the research on the regional diversity of Polish. The comparison of the register of 19th-century Modern Polish regionalisms, which I compiled, with the provincialisms recorded in SR showed that, although the dictionary only included 176 of the analysed units, it also collected 27 new units, not recorded at all or not classified as elements of regional Polish in any of the dictionary publications I analysed. Hence, the results prove that SR is an interesting material base for lexicological research on regional Polish.